The value relevance of accounting measures based on international financial reporting standards (IFRS) before, during and after hyperinflation period in Zimbabwe - Makaya, Martin (Department of Finance and Tax, 2018)
This study examines the value relevance of International Financial Reporting Standards (IFRS) based accounting measures for the periods before, during and after hyperinflation in Zimbabwe. The study uses a sample of 30 listed companies for the entire period from 1996 to 2013. It uses the fixed effects (FE) technique to examine the value relevance of IFRS based accounting numbers using the price model as the main tool for analysis and thereafter, the returns model as an additional tool for further analysis to this study Using the price model, the results show that IFRS based accounting measures in the form of earnings per share (EPS) and book value of equity per share (BVPS) are more value relevant before and during the hyperinflation periods relative to the after-hyperinflation period using the share prices 4 months after year end as proxies for firm value. The results also show that EPS is more value relevant before and during the hyperinflation period where as BVPS is not. The results further show that both EPS and BVPS are not value relevant for the period after hyperinflation when share prices 4 months after year end are used in the analysis. Further tests under the price model show no change in the conclusions reached if share prices 5 and 6 months after year end are used. Furthermore, tests based on a year on year analysis show that IFRS based accounting measures were more value relevant before and during the hyperinflation period relative to the after the hyperinflation period. In addition, for the period during hyperinflation, the year on year analysis shows that the EPS measure was value relevant for all the years while the BVPS was not for the years 2003 and 2005. A further test on whether historical cost IFRS based accounting measures are more value relevant than inflation adjusted IFRS based accounting measures (used in the main analysis) was also conducted for the period during hyperinflation (i.e. 2000-2005 only). The results based on this analysis show that both historical cost and inflation adjusted IFRS based accounting measures are value relevant during a hyperinflationary period irrespective of whether share prices 4, 5 or 6 months are used as proxies for firm value. Thus, this finding shows that historical cost and inflation adjusted accounting information should be used as complements and not as substitutes for each other. Using the returns model under additional analysis, the results further show that the accounting measures were more value relevant before and during the hyperinflation periods relative to the after-hyperinflation period. The results also show that EPS was value relevant before and during hyperinflation irrespective of whether share returns 4, 5 or 6 months after year end were used in the analysis. In addition, further tests based on the returns model show that both historical cost and inflation adjusted sets of accounting measures are value relevant for share valuation purposes during the hyperinflation period. This finding confirms that both historical cost and inflation adjusted accounting measures are value relevant and thus should be used jointly.